Using Microsoft Word, Part Five … Help for the Bewildered Writer. - West, Cohn G. (Writers' Journal)
The article focuses on the use of ALT plus four numbers to produced accented letters to emails using Microsoft Word in personal computers. The technique could be used only with the numbers on the Number Pad. A complete lists of the Shortcuts are provided for users of Mac computers for easy way to produce the most accented letters